2011
DOI: 10.1016/j.molcel.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of ATM-Dependent Monoubiquitylation of Histone H2B for Timely Repair of DNA Double-Strand Breaks

Abstract: In the above article, we inadvertently provided the wrong catalog numbers for two monoclonal antibodies generated by Sigma Aldrich against the proteins RNF20 and RNF40. The correct catalog numbers are XYZ for the RNF20 antibody and ABC for the RNF40 antibody. The Supplemental Information file has been updated online and now includes these correct catalog numbers. We regret any inconvenience this may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
111
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(117 citation statements)
references
References 0 publications
5
111
0
1
Order By: Relevance
“…Intriguingly, we found that the levels of H2Bub1 are strikingly decreased after erastin treatment, suggesting that H2Bub1 may be involved in the regulation of ferroptosis ( Fig 1A). In addition to knockdown of RNF20 expression, we and others previously indicated that overexpression of the K120R mutant of H2B (H2BK120R) can also downregulate the levels of endogenous H2Bub1 making a useful way to examine the roles of H2Bub1 [44,45]. In addition to knockdown of RNF20 expression, we and others previously indicated that overexpression of the K120R mutant of H2B (H2BK120R) can also downregulate the levels of endogenous H2Bub1 making a useful way to examine the roles of H2Bub1 [44,45].…”
Section: Loss Of H2bub1 Significantly Sensitizes Cells To Erastin-indmentioning
confidence: 99%
“…Intriguingly, we found that the levels of H2Bub1 are strikingly decreased after erastin treatment, suggesting that H2Bub1 may be involved in the regulation of ferroptosis ( Fig 1A). In addition to knockdown of RNF20 expression, we and others previously indicated that overexpression of the K120R mutant of H2B (H2BK120R) can also downregulate the levels of endogenous H2Bub1 making a useful way to examine the roles of H2Bub1 [44,45]. In addition to knockdown of RNF20 expression, we and others previously indicated that overexpression of the K120R mutant of H2B (H2BK120R) can also downregulate the levels of endogenous H2Bub1 making a useful way to examine the roles of H2Bub1 [44,45].…”
Section: Loss Of H2bub1 Significantly Sensitizes Cells To Erastin-indmentioning
confidence: 99%
“…In addition to H2A ubiquitylation, also H2B ubiquitylation (at K120) was recently recognized to play a role in the DDR (Moyal et al., 2011; Nakamura et al., 2011). During transcription, H2B ubiquitylation (uH2B) is carried out by the RNF20/RNF40 complex (Pavri et al., 2006).…”
Section: Histone Modificationsmentioning
confidence: 99%
“…During transcription, H2B ubiquitylation (uH2B) is carried out by the RNF20/RNF40 complex (Pavri et al., 2006). Likewise, RNF20/40‐induced uH2B is directly involved in the DDR and promotes DNA repair by both HR and NHEJ (Moyal et al., 2011; Nakamura et al., 2011). RNF20/40 is directly recruited to DSBs and damage‐induced uH2B requires ATM‐mediated phosphorylation of RNF20/40 (Moyal et al., 2011).…”
Section: Histone Modificationsmentioning
confidence: 99%
See 2 more Smart Citations